Site-Specific Glycan-Masking/Unmasking Hemagglutinin Antigen Design to Elicit Broadly Neutralizing and Stem-Binding Antibodies Against Highly Pathogenic Avian Influenza H5N1 Virus Infections - Chen, Ting-Hsuan; Yang, Ya-Lin; Jan, Jia-Tsrong; Chen, Chung-Chu; Wu, Suh-Chin (Frontiers in Immunology, 2021)
The highly pathogenic avian influenza (HPAI) H5N1 viruses with the capability of transmission from birds to humans have a serious impact on public health. To date, HPAI H5N1 viruses have evolved into ten antigenically distinct clades that could cause a mismatch of vaccine strains and reduce vaccine efficacy. In this study, the glycan masking and unmasking strategies on hemagglutinin antigen were used for designing two antigens: H5-dm/st2 and H5-tm/st2, and investigated for their elicited immunity using two-dose recombinant H5 (rH5) immunization and a first-dose adenovirus vector prime, followed by a second-dose rH5 protein booster immunization. The H5-dm/st2 antigen was found to elicit broadly neutralizing antibodies against different H5N1 clade/subclade viruses, as well as more stem-binding antibodies to inhibit HA-facilitated membrane fusion activity. Mice immunized with the H5-dm/st2 antigen had a higher survival rate when challenged with homologous and heterologous clades of H5N1 viruses. Mutant influenza virus replaced with the H5-dm/st2 gene generated by reverse genetics (RG) technology amplified well in MDCK cells and embryonated chicken eggs. Again, the inactivated H5N1-dm/st2 RG virus elicited more potent cross-clade neutralizing and anti-fusion antibodies in sera. Therefore, the H5N1-dm/st2 RG virus with the site-specific glycan-masking on the globular head and the glycan-unmasking on the stem region of H5 antigen can be used for further development of cross-protective H5N1 vaccines.